(untitled) (Revista Contexto & Saúde, 2025)
This study objective was to define the construct of health professionals working in the pediatric ward, regarding the Global Patient Safety Challenge (DGSP) “Medication without Harm”. This is a cross-sectional and observational study, which included 48 health professionals who work in pediatrics at a university hospital located in the state of São Paulo, Brazil. A questionnaire was applied, which included the characteristics of professionals and the four DGSP domains: Professionals, Medications, Patients and public, Systems, and practices. Factor analysis was performed, with rotation using the Varimax method, and Cronbach’s alpha was calculated. The results revealed the median age of health professionals was 39 years old, with 89.6% being female at birth. Two dimensions were identified: (1) checking, registration, and information; and (2) reports from patients and family members, with Cronbach’s alpha of 0.8598. It was concluded that health professionals consider it important to inform patients and family members, check solutions labels, understand reports from children and family members, and check the medication dispensed by the pharmacy. The construct did not include the domains of professionals and medications, which may represent weaknesses in the medication process in the pediatric ward studied. These weaknesses refer to training, communication failures, knowledge about previously occurring adverse events, discrepancies between prescriptions, labels, packaging, and keeping medications that are not being used by the patient at the bedside. The clarity of medical prescriptions was also not included in the construct, and its improvement is another important opportunity for improvement.